The elements of the everyday life of the Ukrainian / Ruthenian community in the 19th century in the light of the “Wisła” magazine - Czerniak, Grażyna (Marginesy, 2021)
The present text aims to organize and approximate the information which concerns the Ukrainian society in XIX century that was shown in ethnographic magazine „Wisła”. Thanks to thorough field research, documented in the periodical, readers have been informed that even then people had noticed the differences among the representatives of Ruthenians. Those differences can be seen in architecture, culinary culture and spirituality. In the present thesis the author attempts to capture and organize this cultural mosa.